Bark Transpiration Rates Can Reach Needle Transpiration Rates Under Dry Conditions in a Semi-arid Forest - Lintunen, Anna; Preisler, Yakir; Oz, Itay; Yakir, Dan; Vesala, Timo; Hölttä, Teemu (Frontiers in Plant Science, 2021)
Drought can cause tree mortality through hydraulic failure and carbon starvation. To prevent excess water loss, plants typically close their stomata before massive embolism formation occurs. However, unregulated water loss through leaf cuticles and bark continues after stomatal closure. Here we studied the diurnal and seasonal dynamics of bark transpiration and how it is affected by tree water availability. We measured continuously for six months water loss and CO2 efflux from branch segments and needle-bearing shoots in Pinus halepensis growing in a control and an irrigation plot in a semi-arid forest in Israel. Our aim was to find out how much passive bark transpiration is affected by tree water status in comparison to shoot transpiration and bark CO2 emission that involve active plant processes, and what is the role of bark transpiration in total tree water use during dry summer conditions. Maximum daily water loss rate per bark area was 0.03–0.14 mmol m-2 s-1, which was typically ~76% of the shoot transpiration rate (on leaf area basis), but could even surpass the shoot transpiration rate during the highest evaporative demand in the control plot. Irrigation did not affect bark transpiration rate. Bark transpiration was estimated to account for 64–78% of total water loss in drought-stressed trees, but only for 6–11% of the irrigated trees, due to differences in stomatal control between the treatments. Water uptake through bark was observed during most nights, but it was not high enough to replenish the lost water during the day. Unlike bark transpiration, branch CO2 efflux decreased during drought due to decreased metabolic activity. Our results demonstrate that although bark transpiration represents a small fraction of the total water loss through transpiration from foliage in non-stressed trees, it may have a large impact during drought.